Multidisciplinary approach to a subgingivally fractured incisor tooth: A case report - Doğu Ömür Dede; Emine Şen Tunç; Ahmet Umut Güler; Sebahat Yazicioğlu (Elsevier, 2017)
This case report describes a multidisciplinary approach using orthodontic forced eruption to facilitate prosthetic restoration of a subgingivally fractured maxillary permanent central incisor. A 14-year-old male patient presented at the pediatric dental clinic due to unesthetic appareance and for management of a fractured maxillary right central incisor tooth. Intraoral examination revealed that the maxillary right central incisor had sustained a crown-root fracture with pulp exposure. We treated the tooth endodontically and performed orthodontic root extrusion with a modified Hawley appliance prior to prosthetic rehabilitation. Approximately 2-3 mm of extrusion of the tooth was obtained within 8 weeks. A fiber post was then inserted into the root canal, and final restoration was completed with an all-ceramic crown. Follow-up 18 months after treatment revealed good periodontal health, esthetics and normal function.